Pengelolaan Koleksi Langka di Dinas Kearsipan dan Perpustakaan Kota Jambi - Akhiria, Nova Sari; Yenti, Zarfina; Yusufhin, Fridinanti (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2024)
The purpose of this study was to determine the management, constraints and efforts to manage rare collections at the Jambi City Archives and Library Service. This research uses qualitative research, descriptive research approach, with data collection techniques of observation, interviews and documentation. The data analysis method used is data collection, data reduction, data presentation and drawing conclusions. During the observation of the Jambi City Archives and Library Service, there were rare collections that did not appear to have received preservation or treatment. In this study using the theory from Sutarno's book title library management. Rare Collection Management at the Jambi City Archives and Library Service shows that rare collection management is carried out with several activities, namely: 1. selection of rare collections by taking from the deposit collection, classifying rare collections using DDC, cataloging using the InlisLite application, labeling books, to storing rare collections in the reference room. 2. The obstacles experienced by library staff in managing rare collections are: Unstructured grouping of rare collections, and also no special room for rare collections, lack of human resources (Human Resources) who understand in repairing library materials and lack of tools to repair library materials, lack of library users' awareness of maintaining rare collections. 3. Efforts to overcome obstacles in managing rare collections at the Jambi City Archives and Library Service, namely: Making efforts to provide a special place for rare collections, conducting training to add insight in terms of knowing how to input data Keywords: Management, rare collections, Jambi City Archives and Library Service